2015
DOI: 10.5459/bnzsee.48.2.100-117
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental dampers in base-isolated buildings to mitigate large isolator displacement under earthquake excitations

Abstract: The effect of viscous, viscoelastic, and friction supplemental dampers on the seismic response of base-isolated building supported by various isolation systems is investigated. Although base-isolated buildings have an advantage in reducing damage to the superstructure, the displacement at the isolation level is large, especially under near-fault ground motions. The influence of supplemental dampers in controlling the isolator displacement and other responses of base-isolated building is investigated using a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…In addition, the stroke length of the nontraditional TMD is greatly reduced as compared with the traditional TMD during near‐fault long‐period earthquakes. Alternatively, Zelleke et al proposed supplemental dampers to effectively control the bearing displacement of the base‐isolated buildings subjected to near‐fault ground motions. However, Hessabi et al concluded that the effectiveness of the TMDs in base‐isolated structures with nonlinear base isolation systems is not as significant as for the linear base isolation systems.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stroke length of the nontraditional TMD is greatly reduced as compared with the traditional TMD during near‐fault long‐period earthquakes. Alternatively, Zelleke et al proposed supplemental dampers to effectively control the bearing displacement of the base‐isolated buildings subjected to near‐fault ground motions. However, Hessabi et al concluded that the effectiveness of the TMDs in base‐isolated structures with nonlinear base isolation systems is not as significant as for the linear base isolation systems.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded peak response of the BI building with and without TMD schemes for the generated number of ground motions (N gen ) are then compared with the corresponding seismic demands. Thereafter, the probability of failure P f at any certain PGA level is defined as following (19) where N fail denotes the number of the cases which satisfies Equation (18). Then the process is reiterated for the range of the above-mentioned PGA levels, and the respective fragility curves are achieved assuming a lognormal distribution.…”
Section: Seismic Fragility Analysismentioning
confidence: 99%
“…As a consequence of added flexibility, displacement demand on the structure gets amplified, and additional damping is provided to keep displacement demand within acceptable limits. Zelleke et al [18] studied the effectiveness of viscous and visco-elastic dampers on seismic response control of BI buildings. They found that there is a tradeoff between the extent to which acceleration and displacement demand can be controlled by BI system combined with additional damping devices.…”
Section: Introductionmentioning
confidence: 99%
“…The utilized isolation system is composed of elastomeric isolators with lead core inside. Their behavior has been simulated in the analysis by multi-linear non-elastic model (see [12,23]), which is defined by the following parameters: Effective stiffness (K eff ), effective damping (C eff ), initial stiffness (K 1 ), and yield force (f y ). The values of these parameters for the structural models of five-story and eight-story buildings are presented in Table 1.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The situation can be somewhat improved by the application of some methods of reduction of excessive displacements at the isolation level. Zelleke et al [23], for example, proposed to use the supplemental dampers in order to reduce the structural displacements without significant increase in the forces transferred to the superstructure. A structural vibration control system composed of rubber bearing with magnetorheological damper was considered by Fu et al [24].…”
Section: Introductionmentioning
confidence: 99%